الشيخ محمود البرزنجي وجهوده لقيام دولة كوردستان Sheikh Mahmoud Barzanji and his Efforts for the Establishment of the Kurdistan - (Kemal Rashid), كمال طاهر رشيد; (Mohamed Ruslan), محمد روسلان; (Feisal AbdulHamid), فيصل عبد الحميد (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
الملخص تهدف هذه الدراسة إلى إلقاء الضوء على حقبة مهمة من تاريخ كوردستان، بعد الحرب العالمية الأولى التي عانت خلالها المنطقة من فراغ سياسي وإداري، تم ملؤه بظهور قائد عرف باسم الشيخ محمود البرزنجي. وقد ذاع صيت الشيخ في فترة شهدت العديد من الأحداث السياسية الجسيمة، فضلاً عن المحاولات العديدة لدول الشرق والغرب للهيمنة على كوردستان بعد نهاية الخلافة العثمانية. وقد ترعرع الشيخ محمود البرزنجي في أسرة متدينة عرفت ببراعتها في العلوم الشرعية ونضالها السياسي والعسكري. وقام البريطانيون بمساندة دعوته لتأسيس مملكة كوردية، وكانوا يهدفون من وراء ذلك إضعاف أثر السلطة العثمانية في المنطقة. فيما اصطدم الشيخ محمود البرزنجي فيما بعد مع البريطانيين والروس أيضاً، وفي عام 1918م تم تنصيبه ملكاً لكوردستان. وقد جرت مراسيم الإعلان عن حكومته ثلاث مرات، ثم سقطت مملكة كوردستان في عام 1925م وأصبحت جزءاً من مملكة العراق. وقد توصلت الدراسة إلى العديد من النتائج أهمها أنّ الشيخ محمود البرزنجي بقي ثابتاً على مبادئه ولم يتخل عنها مقابل الإغراءات المالية التي قدمها له الأتراك والبريطانيون، كما أثبت الشيخ محمود البرزنجي أنه شخصية ديموقراطية، حيث سعى جاهداً لتمثيل طوائف المجتمع الكوردي ومكوناته كافة في حكومته بما فيهم غير المسلمين. كما سعى الشيخ محمود البرزنجي جاهداً للتعاون مع مسلمي المنطقة، حيث ساعد الأتراك في حربهم ضد الروس، كما ساند العرب في جنوب العراق عسكرياً في حربهم ضد البريطانيين. الكلمات المفتاحية: محمود البرزنجي، كوردستان، نضال الكورد، البرزنجييون، الاحتلال البريطاني. ********************************************************* Abstract This study aims at shedding light on an important era after the First World War in the history of Kurdistan during which the region suffered from political and administrative vacuum and it was filled by the emergence of the leader known as Sheikh Mahmoud Barzanji. He shot to renown in the period that witnessed many serious political events as well as numerous attempts of many of Eastern and Western countries to dominate the Kurdistan after the end of the Ottoman Empire. Sheikh Mahmoud Barzanji grew up in a religious family known for its agility in Islamic SharÊ‘ah sciences and political and military struggle. The British supported his call for the establishment of the Kurdish Kingdom and their aim behind this support was to weaken the Ottoman power in the region. Later on Sheikh Mahmoud Barzanji collided with both the British and Russia, and in year 1918 he was ushered in as the king of Kurdistan. His government announced decrees three times and the Kingdom of Kurdistan fell in 1925 and became part of the Kingdom of Iraq. This study found many important results. The most significant findings show that Sheikh Mahmoud Barzanji remained firm on his principles and refused to abandon them against the financial incentives offered to him by the Turks and the British. Sheikh Mahmoud Barzanji proved to be a democratic person as he struggled for the representation of all sects of the Kurdish community and all of its components in his government, including non-Muslims. He also worked hard to cooperate with the Muslims of the region as he supported the Turks in their war against the Russians and the Arab the southern Iraq against the British. Keywords: Mahmoud Barzanji, Kurdistan, struggle of the Kurds, Alborznjiyon, British occupation.